Do Stages of Change Readiness and Treatment Eagerness Scale (SOCRATES) Scores Predict Readmission to an Inpatient Substance Abuse Treatment Program for Adolescents?. Issue 6 (1st November 2016) - Doerfler, Leonard A.; Melle, Daniel; McLaughlin, Thomas; Fisher, William H.
ABSTRACT: This study investigated factors associated with readmission to an inpatient treatment program for adolescents with substance abuse disorders. Participants were 546 adolescents (68% male, N = 372). Mean age was 16.0 years. Approximately 12% of adolescents treated in this program were readmitted for a second episode of treatment. The average time to readmission for these adolescents was approximately three months (median = 82.5 days, mean = 107 days). Participants completed the Stages of Change Readiness and Treatment Eagerness Scale (SOCRATES; Miller & Tonigan, 1996 ) at admission and discharge. Based on previous research, it was hypothesized that adolescents' level of readiness to change at the end of the initial inpatient treatment episode would predict readmission for additional inpatient treatment. The findings for this study did not support this hypothesis. Adolescents readmitted for a second episode of treatment did not differ from adolescents who were not readmitted on any SOCRATES subscale score at time of initial admission for inpatient treatment. Moreover, there were no differences between these groups when these adolescents completed the first episode of inpatient treatment. Overall, the present findings indicate that adolescents' readiness to change, or level of motivation, when discharged from inpatient treatment is not associated with the likelihood of readmission for additional inpatient substance abuse treatment.